Peran Studi Perbandingan Hukum Tata Negara dalam Memperbaiki Kualitas Legislasi di Indonesia - Muhamad Arya Wijaya (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the role of comparative constitutional law studies in improving the quality of legislation in Indonesia, with a focus on the legislative drafting process and institutional dynamics. The study employs a qualitative approach using a case study design, utilizing data collection techniques such as semi-structured interviews, document analysis, and limited observation of the legislative process. Informants include legislative drafters, constitutional law scholars, and public policy practitioners, selected through purposive sampling and expanded via snowball sampling. The research findings indicate that the use of comparative law studies remains ad hoc and has not been systematically integrated, and there are weaknesses in the integration between the comparative approach, public participation, and institutional capacity. Nevertheless, the comparative approach holds significant potential for enhancing the clarity, consistency, and enforceability of legal norms. These findings contribute to a stronger understanding that comparative constitutional law is an important instrument in institutional learning and legislative reform. This study concludes that the systematic integration of comparative law studies into the legislative process is necessary to improve the quality of regulations, with implications for strengthening institutional capacity and reforming legislative procedures; it also recommends further research to examine comparative practices in other countries and empirically measure their impact.